Flexible Manipulation of Emitting Beams Using Single‐Aperture Circularly Polarized Digital Metasurface Antennas: Multi‐Beam Radiation toward Vortex‐Beam Generation. Issue 4 (13th February 2020) - Nadi, Morteza; Rajabalipanah, Hamid; Cheldavi, Ahmad; Abdolali, Ali
Abstract: As the technological demands for multiple‐input multiple‐output communication systems increasingly grow, there is a critical need for the next generation of multi‐beam radiators. The concept of single‐feed compact phase‐encoded metasurface antennas is introduced, the radiation specifications of which can be flexibly manipulated to provide circularly‐polarized single‐, dual‐, quad‐beam far‐field patterns, a circularly‐polarized optical angular momentum‐carrying beam, and a circularly‐polarized quasi‐omnidirectional emission. With a small footprint area at f = 5.8 GHz, the proposed circularly polarized coding metasurface antenna (CPCMA) consists of several radiating meta‐atoms with 2‐bit excitation phases of 0, π/2, π, and 3π/2. Compared with conventional antenna arrays, the center‐to‐center distance of the coding elements is noticeably reduced, where periodic boundary conditions have been employed to analyze the inter‐element coupling effects. A low‐cost and simple corporate feed network is also designed to implement the required coding mask of each CPCMA type. To verify the performance of the proposed CPCMA, a prototype is fabricated and measured. Proof‐of‐concept experiments demonstrate excellent agreement with numerical simulations and theoretical predictions. This constructs a bridge between conventional arrays and digital metasurfaces, providing a powerful host for the next generation of multi‐beam circularly polarized radiators. Abstract : A circularly‐polarized digital metasurface antenna is proposed in which different intriguing functionalities from single beam radiation toward optical angular momentum mode generation can be acquired using a single aperture. This coding metasurface is compact and ultra‐thin (0.03 λ ) and it is fed by a microstrip transmission line network without need for any external circularly‐polarized source imposing assembly or shadow problems.